2018
DOI: 10.1590/1678-7757-2017-0215
|View full text |Cite
|
Sign up to set email alerts
|

Debris extrusion and foraminal deformation produced by reciprocating instruments made of thermally treated NiTi wires

Abstract: ObjectiveTo evaluate the amount of apically extruded debris, percentage of foraminal enlargement and apical foramen (AF) deformation that occurred during root canal preparation with different reciprocation systems: Reciproc, WaveOne (M-Wire), and ProDesign R (Shape Memory Technology Wire) at two different working lengths (WLs): 0.0 and 1.0 mm beyond the AF.Material and methodsThe AF of 120 root canals in 60 mesial roots of mandibular molars were photographed with stereomicroscope and randomly assigned into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 25 publications
0
27
2
4
Order By: Relevance
“…There are no reports on the shaping ability of PDR instruments; however, Frota et al . () reported that PDR had a lower rate of foraminal deformation in comparison to Reciproc and WaveOne, which indicates a suitable centring ability. Although the results revealed a satisfactory maintenance of the canal trajectory, it can be observed in Table that all systems had a tendency of root canal transportation towards the external root canal walls, regardless of the instrument diameter, which can also be observed in Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There are no reports on the shaping ability of PDR instruments; however, Frota et al . () reported that PDR had a lower rate of foraminal deformation in comparison to Reciproc and WaveOne, which indicates a suitable centring ability. Although the results revealed a satisfactory maintenance of the canal trajectory, it can be observed in Table that all systems had a tendency of root canal transportation towards the external root canal walls, regardless of the instrument diameter, which can also be observed in Fig.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, heat-treated instruments tend to have a greater centring ability than conventional NiTi alloys(Duque et al 2017, Ozy€ urek et al 2017, B€ urklein et al 2018. There are no reports on the shaping ability of PDR instruments; however,Frota et al (2018) reported that PDR had a lower rate of foraminal deformation in comparison to Reciproc and WaveOne, which indicates a suitable centring ability.Although the results revealed a satisfactory maintenance of the canal trajectory, it can be observed in…”
mentioning
confidence: 99%
“…1,11,12 However, with the development of different designs and heat treatments for nickel-titanium alloys and their consequent superelasticity, faster access to the foramen, and possible foraminal enlargement became important factors to be considered in the amount of debris that can be apically extruded. 13 With the introduction of different reciprocating single-file instrumentation systems, it is important to analyze the behavior of these instruments during root canal preparation, and an aspect lacking scientific evidence is the amount of extruded debris. 13 Therefore, this study aimed to quantify the amount of debris apically extruded after instrumentation with ProDesign R (Easy Equipamentos; Belo Horizonte, Minas Gerais, Brazil) and Reciproc Blue (VDW; Munich, Germany) reciprocating systems.…”
Section: Introductionmentioning
confidence: 99%
“…13 With the introduction of different reciprocating single-file instrumentation systems, it is important to analyze the behavior of these instruments during root canal preparation, and an aspect lacking scientific evidence is the amount of extruded debris. 13 Therefore, this study aimed to quantify the amount of debris apically extruded after instrumentation with ProDesign R (Easy Equipamentos; Belo Horizonte, Minas Gerais, Brazil) and Reciproc Blue (VDW; Munich, Germany) reciprocating systems. The null hypothesis was that the two systems would not differ in the quantity of apically extruded debris.…”
Section: Introductionmentioning
confidence: 99%
“…PDL uses s CM alloy and SRF utilizes a Blue alloy. BTR has a conventional NiTi alloy, and several studies have demonstrated that heat-treated NiTi have greater flexibility and better maintenance of the canal path than do conventional alloys FROTA et al, 2018;.…”
Section: Discussionmentioning
confidence: 99%